PENGARUH KONVERGENSI IFRS, MEKANISME GOOD CORPORATE GOVERNANCE DAN REPUTASI KANTOR AKUNTAN PUBLIK TERHADAP PENYAMPAIAN LAPORAN KEUANGAN TAHUNAN PADA PERUSAHAAN PUBLIK PERAIH CGPI AWARDS PERIODE 2011-2012 - Kurniawati Kurniawati (Jurnal Akuntansi Bisnis, 2017)
This research aimed to examine the effect of IFRS Convergence, Good Corporate Governance mechanism and the reputation of public accounting firm to submission of financial statements (measured by Financial Reporting Lead Time - FRTL). Board of commissioner size and audit committee used as a proxy from good corporate governance mechanism, as well as IFRS Convergence and the reputation of public accounting firm are used as independent variables in this research. The sample used in this research were company listed at Indonesia Stock Exchange that obtained scores in the ranking as Indonesia Most Trusted Companies 2011-2012 by Corporate Governance Perception Index (CGPI). Samples are collected by purposive sampling and resulted in 20 firms as the final sample. The statistic method used was multiplied analysis linear regression, with hypotheses testing of statistic t tests (α = 5%).The results of this research showed that the board of commissioner size and the reputation of public accounting firm has a significant influence to the financial reporting lead time, while IFRS Convergence and audit committee has no significant influence to the financial reporting lead time. Keyword: International Financial Reporting Standards (IFRS) Convergence, Financial Reporting Lead Time, Board of commissioner size, reputation of public accounting firm, audit committee.